Home My Page Projects Code Snippets Project Openings diderot
Summary Activity Tracker Tasks SCM

SCM Repository

[diderot] Diff of /branches/charisee_dev/src/compiler/high-il/normalize-ein.sml
ViewVC logotype

Diff of /branches/charisee_dev/src/compiler/high-il/normalize-ein.sml

Parent Directory Parent Directory | Revision Log Revision Log | View Patch Patch

revision 2450, Thu Oct 3 20:17:08 2013 UTC revision 2452, Sat Oct 5 00:43:58 2013 UTC
# Line 4  Line 4 
4      local      local
5    
6      structure E = Ein      structure E = Ein
7    (* structure P=Printer*)      structure P=Printer
8    
9      in      in
10    
# Line 29  Line 29 
29                  (* end case *)                  (* end case *)
30       end       end
31    
32  (*  
33  fun mkProd [e]=(1,e)  fun mkProd [e]=(1,e)
34      | mkProd(e)=let      | mkProd(e)=let
35      fun flatten(i,((E.Prod l)::l'))= flatten(1,l@l')      fun flatten(i,((E.Prod l)::l'))= flatten(1,l@l')
36          |flatten(i,((E.Const c):: l'))=          |flatten(i,((E.Const c):: l'))=
37             if(c>0.0 orelse c<0.0) then                  if(c>0.0 orelse  0.0>c) then (3,[E.Const 0.0])
38                 if (c>1.0 orelse c<1.0) then let                  else flatten(i,l')
                 val(b,a)=flatten(i,l') in (b,[E.Const c]@a) end  
                else flatten(1,l')  
             else (3, [E.Const(0.0)])  
39           | flatten(i,[])=(i,[])           | flatten(i,[])=(i,[])
40           | flatten (i,e::l') =  let           | flatten (i,e::l') =  let val(a,b)=flatten(i,l') in (a,[e]@b) end
41                      val(b,a)=flatten(i,l') in (b,[e]@a) end       val (change,a)=flatten(0,e)
42       val ( b,a)=flatten(0,e)       in if(change=3) then (1,E.Const(0.0))
      in if(b=3) then (1,E.Const(0.0))  
43          else case a          else case a
44          of [] => (1,E.Const(0.0))          of [] => (1,E.Const(0.0))
45          | [e] => (1,e)          | [e] => (1,e)
46          | es => (b, E.Prod es)          | es => (change, E.Prod es)
47          (* end case *)          (* end case *)
48           end           end
49    
50    (*
51    
52  fun mkEps(e)= (case e  fun mkEps(e)= (case e
53      of E.Apply(E.Partial [E.V a], E.Prod( e2::m ))=> (0,e)      of E.Apply(E.Partial [E.V a], E.Prod( e2::m ))=> (0,e)
# Line 65  Line 62 
62      |_=> (0,e)      |_=> (0,e)
63      (*end case*))      (*end case*))
64    
65  fun mkApply(E.Apply(d, e)) = (case e  
     of E.Tensor(a,[])=> (0,E.Const(0.0))  
      | E.Tensor _=> (0,E.Apply(d,e))  
      | E.Const _=> (1,E.Const(0.0))  
      | E.Add l => (1,E.Add(List.map (fn e => E.Apply(d, e)) l))  
      | E.Sub(e2, e3) =>(1, E.Sub(E.Apply(d, e2), E.Apply(d, e3)))  
      | E.Prod((E.Epsilon c)::e2)=> mkEps(E.Apply(d,e))  
      | E.Prod[E.Tensor(a,[]), e2]=>  (0, E.Prod[ E.Tensor(a,[]), E.Apply(d, e2)]  )  
      | E.Prod((E.Tensor(a,[]))::e2)=>  (0, E.Prod[E.Tensor(a,[]), E.Apply(d, E.Prod e2)] )  
      | E.Prod es =>    (let  
            fun prod [e] = (E.Apply(d, e))  
               | prod(e1::e2)=(let val l= prod(e2) val m= E.Prod[e1,l]  
                    val lr=e2 @[E.Apply(d,e1)]   val(b,a) =mkProd lr  
                 in ( E.Add[ a, m] )  
                 end)  
              | prod _= (E.Const(1.0))  
                 in (1,prod es)  
                 end)  
              | _=> (0,E.Apply(d,e))  
              (*end case*))  
66    
67  fun mkSumApply(E.Sum(c,E.Apply(d, e))) = (case e  fun mkSumApply(E.Sum(c,E.Apply(d, e))) = (case e
68      of E.Tensor(a,[])=> (0,E.Const(0.0))      of E.Tensor(a,[])=> (0,E.Const(0.0))
# Line 106  Line 84 
84      | _=> (0,E.Sum(c,E.Apply(d,e)))      | _=> (0,E.Sum(c,E.Apply(d,e)))
85      (*end case*))      (*end case*))
86    
   
   
 (* Identity: (Epsilon ijk Epsilon ilm) e => (Delta jl Delta km - Delta jm Delta kl) e  
     The epsToDels Function searches for Epsilons in the expression, checks for this identity in all adjacent Epsilons and if needed, does the transformation.  
      The Function returns two separate list, 1 is the remaining list of Epsilons that have not be changed to deltas, and the second is the Product of the remaining expression.  
   Ex:(Epsilon_ijk Epsilon_ilm) Epsilon_stu e =>([Epsilon_stu], [Delta_jl,Delta_km,e -Delta_jm Delta_kl, e] )  
    This is useful since we can normalize the second list without having to normalize the epsilons again.  
         4(Eps Eps)  
        3( Delta_liDelta mj- Delta_mi Delta_lj)  
          Ai-  
87          *)          *)
88    
89    
90                     *)  fun rmEpsIndex(_,_,[])=[]
91    | rmEpsIndex([],[],cs)=cs
92    | rmEpsIndex([],m ,e1::cs)=[e1]@rmEpsIndex(m,[],cs)
93    | rmEpsIndex(i::ix,rest ,(E.V c)::cs)=
94        if(i=c) then rmEpsIndex(rest@ix,[],cs)
95        else rmEpsIndex(ix,rest@[i],(E.V c)::cs)
96    
97    
98    (* Transform eps to deltas*)
99  fun epsToDels(E.Sum(count,E.Prod e))= let  fun epsToDels(E.Sum(count,E.Prod e))= let
100      fun doubleEps((E.Epsilon (a,b,c))::(E.Epsilon(d,e,f))::es,eps,e3)=      fun doubleEps((E.Epsilon (a,b,c))::(E.Epsilon(d,e,f))::es,eps,e3)=
101          let          let
# Line 132  Line 106 
106              (*remove index from original index list*)              (*remove index from original index list*)
107              (*currrent, left, sumIndex*)              (*currrent, left, sumIndex*)
108    
109              fun rmIndex(_,_,[])=[]              val s'= rmEpsIndex([i,s,t,u,v],[],count)
             | rmIndex([],[],cs)=cs  
             | rmIndex([],m ,e1::cs)=[e1]@rmIndex(m,[],cs)  
             | rmIndex(i::ix,rest ,(E.V c)::cs)=  
                    if(i=c) then rmIndex(rest@ix,[],cs)  
                    else rmIndex(ix,rest@[i],(E.V c)::cs)  
   
             val s'= rmIndex([i,s,t,u,v],[],count)  
110              val s''=[E.V s, E.V t ,E.V u, E.V v]              val s''=[E.V s, E.V t ,E.V u, E.V v]
111              val deltas= E.Sub(              val deltas= E.Sub(
112                      E.Sum(s'',E.Prod([E.Delta(E.V s,E.V u), E.Delta(E.V t,E.V v)] @e3)),                      E.Sum(s'',E.Prod([E.Delta(E.V s,E.V u), E.Delta(E.V t,E.V v)] @e3)),
# Line 177  Line 144 
144              |_=> dist(current, eps@[c1],rest))              |_=> dist(current, eps@[c1],rest))
145          end          end
146    
   
   
147      val (es,rest)=findeps([],e)      val (es,rest)=findeps([],e)
148    
149      in      in
150          dist(es,[],rest)          dist(es,[],rest)
151      end      end
152    
 (*  
   
   
   
   
 (*The Deltas then need to be distributed over to the tensors in the expression e.  
 Ex.:Delta ij ,Tensor_j, e=> Tensor_i,e. The mkDelts function compares every Delta in the expression to the tensors in the expressions while keeping the results in the correct order.  
    This also returns a list of deltas and a list of the remaining expression.  
   *)  
   
 fun mkDel(e) = let  
     fun Del(i, [],x)= (i,[],x)  
        | Del(i, d,[])=(i, d,[])  
        | Del(i, (E.Delta(d1,d2))::d, (E.Tensor(id,[x]))::xs)=  
             if(x=d2) then (let  
                val(i',s,t)= Del(i+1,d, xs)  
                in Del(i',s, [E.Tensor(id, [d1])] @t) end)  
             else (let val (i',s,t)= Del(i,[E.Delta(d1,d2)],xs)  
                val(i2,s2,t2)= Del(i',d,[E.Tensor(id,[x])]@t)  
                in (i2,s@s2, t2) end )  
        | Del(i, (E.Delta(d1,d2))::d, (E.Field(id,[x]))::xs)=  
                    if(x=d2) then (let  
                    val(i',s,t)= Del(i+1,d, xs)  
                    in Del(i',s, [E.Field(id, [d1])] @t) end)  
                    else (let val (i',s,t)= Del(i,[E.Delta(d1,d2)],xs)  
                    val(i2,s2,t2)= Del(i',d,[E.Field(id,[x])]@t)  
                    in (i2,s@s2, t2) end )  
   
         | Del(i, d, t)= (i,d,t)  
     fun findels(e,[])= (e,[])  
        | findels(e,es)= let val del1= hd(es)  
             in (case del1  
                of E.Delta _=> findels(e@[del1],tl(es))  
                 |_=> (e, es))  
             end  
     val(a,b)= findels([], e)  
     in  
       Del(0, a, b)  
     end  
   
   
 (*The Deltas are distributed over to the tensors in the expression e.  
  This function checks for instances of the dotProduct.  
 Sum_2 (Delta_ij (A_i B_j D_k))=>Sum_1(A_i B_i) D_k  
 *)  
    fun checkDot(E.Sum(s,E.Prod e))= let  
        fun dot(i,d,r, (E.Tensor(ida,[a]))::(E.Tensor(idb,[b]))::ts)=  
                    if (a=b) then  
                         dot(i-1,d@[E.Sum(1,E.Prod[(E.Tensor(ida,[a])), (E.Tensor(idb,[b]))])], [],r@ts)  
                    else dot(i,d, r@[E.Tensor(idb,[b])],(E.Tensor(ida,[a]))::ts)  
           |dot(i, d,r, [t])=dot(i,d@[t], [], r)  
           |dot(i,d, [],[])= (i,d, [],[])  
           |dot(i,d, r, [])= dot(i,d, [], r)  
           |dot(i, d, r, (E.Prod p)::t)= dot (i, d, r, p@t)  
           |dot(i,d, r, e)= (i,d@r@e, [], [])  
   
         val(i,d,r,c)= dot(s,[],[], e)  
         val soln= (case d of [d1]=>d1  
                    |_=> E.Prod d)  
         in E.Sum(i,soln) end  
       |checkDot(e)= (e)  
   
   
153    
154    fun rmIndex(_,_,[])=[]
155        | rmIndex([],[],cs)=cs
156        | rmIndex([],m ,e1::cs)=[e1]@rmIndex(m,[],cs)
157        | rmIndex(i::ix,rest ,c::cs)=
158            if(i=c) then rmIndex(rest@ix,[],cs)
159            else rmIndex(ix,rest@[i],c::cs)
160    
161    (* Apply deltas to tensors/fields*)
   
                 *)  
   
162  fun reduceDelta(E.Sum(c,E.Prod p))=let  fun reduceDelta(E.Sum(c,E.Prod p))=let
163    
164      fun findDeltas(dels,rest,E.Delta d::es)= findDeltas(dels@[E.Delta d], rest, es)      fun findDeltas(dels,rest,E.Delta d::es)= findDeltas(dels@[E.Delta d], rest, es)
165      | findDeltas(dels,rest,E.Epsilon eps::es)=findDeltas(dels,rest@[E.Epsilon eps],es)      | findDeltas(dels,rest,E.Epsilon eps::es)=findDeltas(dels,rest@[E.Epsilon eps],es)
166      | findDeltas(dels,rest,es)=  (dels,rest,es)      | findDeltas(dels,rest,es)=  (dels,rest,es)
167    
     fun rmIndex(_,_,[])=[]  
         | rmIndex([],[],cs)=cs  
         | rmIndex([],m ,e1::cs)=[e1]@rmIndex(m,[],cs)  
         | rmIndex(i::ix,rest ,c::cs)=  
             if(i=c) then rmIndex(rest@ix,[],cs)  
             else rmIndex(ix,rest@[i],c::cs)  
168    
169      fun distribute(change,d,dels,[],done)=(change,dels@d,done)      fun distribute(change,d,dels,[],done)=(change,dels@d,done)
170          | distribute(change,[],[],e,done)=(change,[],done@e)          | distribute(change,[],[],e,done)=(change,[],done@e)
171          | distribute(change,E.Delta(i,j)::ds,dels,E.Tensor(id,[tx])::es,done)=          | distribute(change,E.Delta(i,j)::ds,dels,E.Tensor(id,[tx])::es,done)=
172              if(j=tx) then distribute(change@[j],dels@ds,[] ,es ,done@[E.Tensor(id,[i])])              if(j=tx) then distribute(change@[j],dels@ds,[] ,es ,done@[E.Tensor(id,[i])])
173              else distribute(change,ds,dels@[E.Delta(i,j)],E.Tensor(id,[tx])::es,done)              else distribute(change,ds,dels@[E.Delta(i,j)],E.Tensor(id,[tx])::es,done)
174        | distribute(change,E.Delta(i,j)::ds,dels,E.Field(id,[tx])::es,done)=
175            if(j=tx) then distribute(change@[j],dels@ds,[] ,es ,done@[E.Field(id,[i])])
176            else distribute(change,ds,dels@[E.Delta(i,j)],E.Field(id,[tx])::es,done)
177          | distribute(change,d,dels,e::es,done)=distribute(change,dels@d,[],es,done@[e])          | distribute(change,d,dels,e::es,done)=distribute(change,dels@d,[],es,done@[e])
178    
179      val (dels,eps,es)=findDeltas([],[],p)      val (dels,eps,es)=findDeltas([],[],p)
# Line 282  Line 184 
184         (change, E.Sum(index,E.Prod (eps@dels'@done)))         (change, E.Sum(index,E.Prod (eps@dels'@done)))
185    end    end
186    
187    fun mkApply2(E.Apply(d,e))=(case e
188        of E.Tensor(a,[])=>(1,E.Const 0.0)
189        | E.Const _ =>(1,E.Const 0.0)
190        | E.Add l => (1,E.Add(List.map (fn e => E.Apply(d, e)) l))
191        | E.Sub(e2, e3) =>(1, E.Sub(E.Apply(d, e2), E.Apply(d, e3)))
192        | E.Prod(E.Tensor(a,[])::e2)=>(1,E.Prod[E.Tensor(a,[]),E.Apply(d,e)])
193        | E.Prod [e1]=>(1,E.Apply(d,e1))
194        | E.Prod es=> (let
195            fun prod [e1] =E.Apply(d,e1)
196            | prod(e1::e2)=(let
197                val l= prod(e2) val m= E.Prod[e1,l]
198                val lr=e2 @[E.Apply(d,e1)] val(b,a) =mkProd lr
199                in  E.Add[a,m]
200                end)
201            in (1,prod es) end)
202        |_=>(0,E.Apply(d,e))
203        (* end case*))
204    
205    fun mkSumApply2(E.Sum(c,E.Apply(E.Partial d,e)))=(case e
206        of E.Const _=>(1,E.Const 0.0)
207        | E.Add l => (1,E.Add(List.map (fn e => E.Sum(c,E.Apply(E.Partial d, e))) l))
208        | E.Sub(e2, e3) =>(1, E.Sub(E.Sum(c,E.Apply(E.Partial d, e2)), E.Sum(c,E.Apply(E.Partial d, e3))))
209        | E.Prod(E.Tensor(a,[])::e2)=>(1, E.Prod[E.Tensor(a,[]),E.Sum(c,E.Apply(E.Partial d,E.Prod e2))])
210        | E.Prod [e1]=>(1,E.Sum(c,E.Apply(E.Partial d,e1)))
211        | E.Prod es =>(let
212            fun prod (change,rest, sum,partial,[]) = (change,E.Sum(sum,E.Apply(E.Partial partial,E.Prod rest)))
213            | prod (change,rest, sum,partial,E.Epsilon(i,j,k)::ps)= let
214                fun matchprod(2,_,_,_)= 1 (*matched 2*)
215                | matchprod(num,_,_,[])=0
216                | matchprod(0,_,_,[eps])=0
217                | matchprod(num,[],rest,eps::epsx)=
218                    matchprod(num,rest,[],epsx)
219                | matchprod(num,E.V p::px,rest,eps::epsx)=
220                    if(p=eps) then matchprod(num+1,px,rest,epsx)
221                    else matchprod(num,px,rest@[E.V p], eps::epsx)
222                | matchprod(num,p::px,rest,eps)=
223                    matchprod(num,px,rest,eps)
224    
225                val change'= matchprod(0,d,[],[i,j,k])
226                in (case change'
227                    of 1 => (1,E.Const 0.0)
228                    | _ =>prod(change,rest@[E.Epsilon(i,j,k)],sum,partial,ps))
229                end
230            | prod (change,rest, sum,partial,E.Delta(i,j)::ps)=let
231                fun applyDelPartial([],_)=(0,[])
232                | applyDelPartial(p::px,r)=
233                    if(j=p) then (1,r@[i]@px)
234                    else  applyDelPartial(px,r@[p])
235    
236                val (change',px)=applyDelPartial(d,[])
237    
238                in (case change'
239                    of 1 => (let val index=rmIndex([j],[],sum)
240                        in prod(1,rest, index,px, ps) end )
241                    | _ => prod(change,rest@[E.Delta(i,j)], sum,partial, ps)
242                    (*end case*)) end
243    
244            | prod (change,rest,sum, partial,e::es)= prod(change,rest@[e],sum,partial,es)
245    
246            val (change,exp) = prod(0,[],c, d, es)
247    
248            in
249                (change,exp)
250            end)
251        | _=>(0,E.Sum(c,E.Apply(E.Partial d,e)))
252            (* end case*))
253    
254    (*
255    E.Sum(c,Apply(d,e))
256        try E.Sum(c,e)=> E.Sum(c',e')
257        ==>    E.Sum(c',E.Apply(d,e'))
258            E.Apply(d,e')=> E.Apply(d',e'')
259        ==>E.Sum(c',E.Apply(d',e'')
260    *)
261    
262  (*Apply normalize to each term in product list  (*Apply normalize to each term in product list
263  or Apply normalize to tail of each list*)  or Apply normalize to tail of each list*)
# Line 298  Line 273 
273                | E.Epsilon _=>body                | E.Epsilon _=>body
274    
275                | E.Neg e => E.Neg(rewriteBody e)                | E.Neg e => E.Neg(rewriteBody e)
276                | E.Add es => let val (b,a)= mkAdd(List.map rewriteBody es)                | E.Add es => let val (change,body')= mkAdd(List.map rewriteBody es)
277                     in if (b=1) then ( changed:=true;a) else a end                     in if (change=1) then ( changed:=true;body') else body' end
278                | E.Sub (a,b)=>  E.Sub(rewriteBody a, rewriteBody b)                | E.Sub (a,b)=>  E.Sub(rewriteBody a, rewriteBody b)
279                | E.Div (a, b) => E.Div(rewriteBody a, rewriteBody b)                | E.Div (a, b) => E.Div(rewriteBody a, rewriteBody b)
280                | E.Partial _=>body                | E.Partial _=>body
# Line 316  Line 291 
291                | E.Prod [E.Partial r1,E.Conv(f,deltas)]=>                | E.Prod [E.Partial r1,E.Conv(f,deltas)]=>
292                     (changed :=true;E.Conv(f,deltas@r1))                     (changed :=true;E.Conv(f,deltas@r1))
293                | E.Prod (E.Partial r1::E.Conv(f,deltas)::ps)=>                | E.Prod (E.Partial r1::E.Conv(f,deltas)::ps)=>
294                     (changed:=true; E.Prod([E.Conv(f,deltas@r1)]@ps))                     (changed:=true;
295                        let val (change,e)=mkProd([E.Conv(f,deltas@r1)]@ps)
296                        in e end)
297                  | E.Prod[(E.Epsilon(e1,e2,e3)), E.Tensor(_,[E.V i1,E.V i2])]=>
298                        if(e2=i1 andalso e3=i2) then (changed :=true;E.Const(0.0))
299                        else body
300    
301                 | E.Prod(E.Partial r1::E.Partial r2::p)=>
302                       (changed:=true;E.Prod([E.Partial(r1@r2)]@p))
303                | E.Prod(e::es)=>let                | E.Prod(e::es)=>let
304                      val e'=rewriteBody e                      val e'=rewriteBody e
305                      val e2=rewriteBody(E.Prod es)                      val e2=rewriteBody(E.Prod es)
306                      in(case e2 of E.Prod p'=> E.Prod([e']@p')                      val(a,b)=(case e2 of E.Prod p'=> mkProd([e']@p')
307                          |_=>E.Prod [e',e2])                          |_=>mkProd [e',e2])
308                        in b
309                     end                     end
310    
311                (*Apply*)                (*Apply*)
312                  | E.Apply(E.Partial [],e)=> e
313                  | E.Apply(E.Partial p, e)=>let
314                        val body'=E.Apply(E.Partial p, rewriteBody e)
315                        val (c, e')=mkApply2(body')
316                    in (case c of 1=>(changed:=true;e')
317                        | _ =>e') end
318                | E.Apply(e1,e2)=>E.Apply(rewriteBody e1, rewriteBody e2)                | E.Apply(e1,e2)=>E.Apply(rewriteBody e1, rewriteBody e2)
319    
320    
321    
322                (* Sum *)                (* Sum *)
323                | E.Sum([],e)=> rewriteBody e                | E.Sum([],e)=> (changed:=true;rewriteBody e)
324                     | E.Sum(_,E.Const c)=>(changed:=true;E.Const c)                     | E.Sum(_,E.Const c)=>(changed:=true;E.Const c)
325                | E.Sum(c,(E.Add l))=> (changed:=true;E.Add(List.map (fn e => E.Sum(c,e)) l))                | E.Sum(c,(E.Add l))=> (changed:=true;E.Add(List.map (fn e => E.Sum(c,e)) l))
326                | E.Sum(c,E.Prod(E.Epsilon eps1::E.Epsilon eps2::ps))=>                | E.Sum(c,E.Prod(E.Epsilon eps1::E.Epsilon eps2::ps))=>
# Line 343  Line 331 
331                          |(0,eps,rest)=>(let                          |(0,eps,rest)=>(let
332                              val p'=rewriteBody(E.Prod rest)                              val p'=rewriteBody(E.Prod rest)
333                              val p''= (case p' of E.Prod p=>p |e=>[e])                              val p''= (case p' of E.Prod p=>p |e=>[e])
334                              in E.Sum(c, E.Prod (eps@p'')) end                              val(a,b)= mkProd (eps@p'')
335                                in E.Sum(c,b) end
336                              )                              )
337                          |_=>body                          |_=>body)
338                     ) end                     end
339                | E.Sum(c, E.Prod(E.Delta d::es))=>let                | E.Sum(c, E.Prod(E.Delta d::es))=>let
340                      val (change,body')=reduceDelta(body)                      val (change,a)=reduceDelta(body)
341                        val (change',body')=(case a
342                            of E.Prod p=> mkProd p
343                            |_=> (0,a))
344                     in (case change of []=>body'|_=>(changed:=true;body')) end                     in (case change of []=>body'|_=>(changed:=true;body')) end
345                  | E.Sum(c,E.Apply(d,e))=>let
346                        val(c',e')=mkSumApply2(body)
347                    in (case c' of 1=>(changed:=true;e') |_=>e')
348                    end
349                | E.Sum(c,e)=>E.Sum(c,rewriteBody e)                | E.Sum(c,e)=>E.Sum(c,rewriteBody e)
350    
351              (*end case*))              (*end case*))
# Line 358  Line 354 
354              val body' = rewriteBody body              val body' = rewriteBody body
355              in              in
356                if !changed                if !changed
357                     then (changed := false; (*print " \n \t => \n \t ";print( P.printbody body');print "\n";*)loop body')                     then (changed := false; print " \n \t => \n \t ";print( P.printbody body');print "\n";loop body')
358                  else body'                  else body'
359              end              end
360      val b = loop body      val b = loop body

Legend:
Removed from v.2450  
changed lines
  Added in v.2452

root@smlnj-gforge.cs.uchicago.edu
ViewVC Help
Powered by ViewVC 1.0.0